ASSESSMENT OF THE STEROID THERAPY EFFECTIVENESS IN COMPLEX TREATMENT OF ACUTE PURULENT RHINOSINUSITIS IN CHILDREN - O. V. Borovikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
Material and methods. The control group consisted of 166 children with acute purulent rhinosinusitis who underwent standard treatment: antibiotic therapy, on the strict condition - endonasal drainage of the maxillary sinuses, the treatment method around Proets, physiotherapy of the nose, vasoconstrictor nose drops. The main group consisted of 132 children with acute purulent rhinosinusitis, who, in addition to standard treatment, were prescribed topical corticosteroid - mometasone furoate. Results. The concentration of lactoferrin (in the main group) was normalized due to the action of the nasonex spray, which proves a high anti-inflammatory effect of the combined treatment. There was a statistically significant difference in the groups after 7 days and 1 month after treatment (t = 1.96; p = 0.05). Based on the data of Mac-Nimar criterion (X2 = 11.204, with the probability of error p = 0.002) in the control group compared to the primary (x2=9.202, with the probability of error p < 0.0001), treatment was less effective. Conclusion. The use of inhalative topical glucocorticosteroid in treatment of children with acute purulent rhinosinusitis allows to achieve a positive clinical effect and the concentration of lactoferrin can serve as an important criterion of the effectiveness of treatment.